Hermetia illucens pupae casings and biogas slurry activated carbon electrodes for Cd2 + removal from aqueous solutions using capacitive deionization - Eva Panja; Tusekile Alfredy; Joyce Elisadiki; Yusufu A.C. Jande (Desalination and Water Treatment)
This study examined capacitive deionisation’s effectiveness for recovering Cd2+ from water using novel carbon-based electrodes derived from Hermetia illucens pupae casings (PC) and biogas slurry (BG). Activated carbon (AC) was produced through carbonization at 500 °C and chemical activation (KOH) at 700 °C. The Brunauer-Emmett-Teller method, Scanning Electron Microscope, X-ray diffractometer, Fourier transform infrared, X-ray photoelectron spectroscopy, Raman spectroscopy, and contact angle measurement were performed on AC. Electrochemical impedance spectroscopy and cyclic voltammetry were used to test the electrochemical properties of carbons. Prepared AC possessed high specific surface areas of 549 m2/g and 927 m2/g for pupae casings and biogas slurry. Electrochemical tests revealed that PC-700 has a high specific capacitance of 271.9 Fg−1 and 105.8 Fg−1 for BG-700. Two concentrations of CdCl2 (5 mg/L and 10 mg/L) were used in a batch mode for the CDI test. Electrodes show an impressive cadmium removal efficiency of approximately 91 % and 56 % for PC and BG electrodes, respectively. Electro-sorption capacity was 10.9 mgg−1 and 2.1 mgg−1 for PC and BG electrodes, respectively. This work demonstrates the potential of PC-derived electrodes in CDI technology for recovering heavy metals from water.